PENAFSIRAN KONSTITUSI DALAM PENGUJIAN KONSTITUSIONALITAS UNDANG- UNDANG TERHADAP UNDANG- UNDANG DASAR 1945 - Lailam, Tanto (Jurnal Media Hukum, 2014)
This study is about interpretation of constitution, this study is based on the extent authority of the Constitutional Court on theÂ  interpretation ofÂ  the constitution,Â  including various verdicts that are considered as controversial.The result of the study shows that Constitution 1945 giving authority of the constitutionÂ  interpretation of the Constitutional Court to evaluate the conflict ofÂ  legal norm, this could be meant that the Constitutional Court is âthe guardian ofÂ  the constitution and the sole interpreting of constitutionâ and as the legitimate interpreter ofÂ  the constitution.Â  SomeÂ  interestingÂ  in implementingÂ  theÂ  interpretation ofÂ  the constitution as aÂ  standardÂ  toevaluateÂ  the conflict ofÂ  legal norm, consists of: First, essentially,Â  that theÂ  interpretation ofÂ  the constitutionÂ  is one of the ways to elaborate understandings contained in constitution text. Second, related to the independence and theÂ  freedom of judge in using an interpretation method whichÂ  is notÂ  regulated by positiveÂ  law, therefore the judge isÂ  free to use those interpretation methods which are appropriate with the conviction of the Justice. JusticeÂ  inÂ  usingÂ  theÂ  interpretation methodÂ  doesnâtÂ  onlyÂ  haveÂ  functionÂ  asÂ  funnel ofÂ  theÂ  act,Â  butÂ  alsoÂ  has functioned as the funnel of justice since a judge is required the value of the law and the sense of justice which exists in the society (substantial justice). Refer toÂ  the theory of living constitution, therefore Constitution 1945 should beÂ  understoodÂ  asÂ  aÂ  constitution which hasÂ  textualÂ  andÂ  contextualÂ  dimentionÂ  Third,Â  theÂ  restrictionÂ  in using the interpretation method, the constitutional judge couldnât only focused into the originalism interpretation method whichÂ  onlyÂ  basedÂ  toÂ  originalÂ  intentÂ  /Â  theÂ  formulationÂ  ofÂ  ConstitutionÂ  1945Â  orÂ  usingÂ  theÂ  other interpretationsÂ  (nonÂ  originalist) which oppositelyÂ  thoseÂ  interpretationÂ  the 1945Â  Constitution doesnât work according to system and/ or contended withÂ  the main idea underlying the constitution itself entirelyÂ  related to theÂ  purpoÂ  seÂ  that wouldÂ  likeÂ  to beÂ  realized.Â  Fourth,Â  theÂ  use ofÂ  interpretation methodÂ  shouldÂ  beÂ  ableÂ  toÂ  be accounted toÂ  the publics, therefore the validity could be examinedÂ  in certain cases. This is very essential to dosince Constitutional Court has an extent interpretation authority so that it could keep justice of Constitutional CourtÂ  to avoid it from misuse of authorityÂ  in interpreting of 1945 Constitution.